Correction: Room temperature iron catalyzed transfer hydrogenation using n-butanol and poly(methylhydrosiloxane). Issue 10 (28th April 2021) - Linford-Wood, Thomas G.; Coles, Nathan T.; Webster, Ruth L.
Abstract : Correction for 'Room temperature iron catalyzed transfer hydrogenation using n -butanol and poly(methylhydrosiloxane)' by Thomas G. Linford-Wood et al., Green Chem., 2021, 23, 2703–2709, DOI: ; 10.1039/D0GC04175K .